Thymectomy in Myasthenia Gravis - Rückert, Jens C.; Swierzy, Marc; Kohler, Siegfried; Meisel, Andreas; Ismail, Mahmoud (Neurology International Open, 2018)
In recent years much progress has been made in the investigation of the pathophysiology, characterizing subgroups, and extension of multimodal treatment of myasthenia gravis (MG). This applies especially to the role of thymectomy (Thx). Thymectomy is always indicated for thymoma-associated myasthenia gravis. Furthermore, based on large cohort studies, during recent decades thymectomy has also become a central part of immune-modulating MG therapy in patients without thymoma. The lack of randomized studies, however, caused a certain persistent reluctance as to the significance of thymectomy. The current MGTX trial has shown the effectiveness of thymectomy. A significant improvement of myasthenic complaints and the reduction of immunosuppressive medication was primarily shown for acquired early-onset MG (EOMG) with complete resection of all thymic tissue. Because the MGTX study only included patients younger than 65 years with generalized MG and positive for acetylcholine-receptor antibodies, at present the significance of Thx for other relevant subgroups as juvenile MG, MG in older patients, ocular MG, as well as seronegative patients is under investigation. Even the prevailing opinion of no benefit of thymectomy for MuSk-positive patients probably needs reevaluation based on ambiguous findings. With respect to surgery, based on the exclusive performance of extended median sternotomy for MG in the MGTX, the value of thoracoscopic modifications for thymectomy as a minimally-invasive alternative is currently under evaluation. For clinical reasons further judgment regarding different minimally-invasive thymectomy techniques compared to the conventional open procedures in the form of randomized comparative studies would be required. Currently, however, an experience-based robotic-assisted thoracoscopic unilateral approach to thymectomy meets all requirements related to surgical, clinical-neurological and patient aspects. Ethical reasons, therefore, will lead to other strategies for comparison of different surgical techniques.
Keywords: Thymectomy; robotic; thoracoscopic; sternotomy; Myasthenia gravis; thymoma